2012
DOI: 10.5539/elt.v5n4p74
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and Personality Traits of TESL Postgraduate Students towards the Use of Information and Communications Technology (ICT) in Second Language Teaching

Abstract: Nowadays technology has practically changed every aspect of language teaching. There are numerous studies focusing on the personality traits of students or other internet users towards the internet utilization. Nonetheless, little research has examined the personality traits of teachers towards using computers for educational purposes especially in the Malaysian context. The purpose of this study was to investigate the motivation and personality traits of TESL postgraduate students in Malaysia towards informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
3
8
1
Order By: Relevance
“…Thus, H2b is not supported. This is in line with a previous local study which found a non-significant impact of conscientiousness towards postgraduate students’ use of ICT (Hassanzadeh et al, 2012). Furthermore, Landers and Lounsbury (2006) also reveal that individuals with lower conscientiousness have a higher Internet usage compared to those with high conscientiousness.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, H2b is not supported. This is in line with a previous local study which found a non-significant impact of conscientiousness towards postgraduate students’ use of ICT (Hassanzadeh et al, 2012). Furthermore, Landers and Lounsbury (2006) also reveal that individuals with lower conscientiousness have a higher Internet usage compared to those with high conscientiousness.…”
Section: Discussionsupporting
confidence: 93%
“…However, if the technology provides ability to improve their social status or opportunities for interpersonal interaction, then they will magnify those beliefs and increase the usage of technology (Lin and Ong, 2010). Recent studies have also found that extraversion has a positive relationship with ICT usage whereby the more extravert individuals have a more positive attitude to use computers (Hassanzadeh et al, 2012). Therefore, it is hypothesized: H2a: Extraversion will positively influence e-filing continuance usage intention.…”
Section: Model Developmentmentioning
confidence: 99%
“…Moreover, the interviewees in the present study possessed three of these four traits. However, these findings were different from Hassanzadeh's (2012) results which reported no significant correlation between Big Five and ICT integration. The different contexts from which the TESL undergraduates grew up can be attributed to this difference.…”
Section: Relationship Between Personality Traits and Ict Integration contrasting
confidence: 99%
“…Two instruments were employed in the study. Firstly, the Personality and Motivation to Integrate ICT Questionnaire was adapted from Isleem (2003), Li (2008) and Hassanzadeh (2012), and it consisted of four sections. Section I was related to demographics, whereas Sections II to IV utilised the Likert scale to elicit data from the participants.…”
Section: Methodsmentioning
confidence: 99%
“…It provides the basic technology for assisting learners to acquire important communication skills, especially in the English language (Hassanzadeh, 2012). ICT is defined as a 'diverse set of technological tools and resources used to communicate, and to create, disseminate, store, and manage information' (Ghasemi & Hashemi, 2011, 3098).…”
Section: Computer Technology and The Internet In Language Teachingmentioning
confidence: 99%